VALUE ADDED TAX (VAT) AND REVENUE ALLOCATION IN NIGERIA - Ordu, Promise Akor; Omesi, Israel (Journal of Contemporary Issues in Accounting, 2022)
The study investigated the relationship between Value added tax revenue and Revenue allocation in Nigeria within the period of 2000-2020. Its specific objective was to ascertain the relationship between VAT and Federal Allocations; ascertain the relationship between VAT and State allocations; and determine the relationship between VAT and Allocations to local governments. Expo facto design was adopted for the study while secondary data was utilized for the study. Data was sourced from Annual Statistical bulletin of Central Bank of Nigeria 2020. The data collected was from the period 2000 – 2020. Descriptive statistics and trend analysis were used for data analysis while Regression was used testing of the hypothesis. The result of the study shows that VAT has a positive and significant relationship with Federal allocation in Nigeria; VAT has a positive and significant relationship with State allocations; VAT has a positive and significant relationship with Local government Allocations in Nigeria The study therefore recommends that Federal government should not be left out in the sharing of VAT revenue as clamoured by some quarters where there is agitation for resource control especially the issue of VAT administration and collection; There should be improved and agreed equitable sharing formula that will ensure that the States and Local governments get more share of the allocation especially as it concerns sharing of the VAT revenue; the Local governments should not be starved of the allocated funds by the states, especially as it concerns their share of VAT and other state allocations.